Layer-resolved electronic behavior in a Kondo lattice system, CeAgAs2. (14th June 2023) - Datta, Sawani; Prakash Pandeya, Ram; Bikash Dey, Arka; Gloskovskii, A; Schlueter, C; Peixoto, T R F; Singh, Ankita; Thamizhavel, A; Maiti, Kalobaran
Abstract: We investigate the electronic structure of an antiferromagnetic Kondo lattice system CeAgAs2 employing hard x -ray photoemission spectroscopy. CeAgAs2, an orthorhombic variant of HfCuSi2 structure, exhibits antiferromagnetic ground state, Kondo like resistivity upturn and compensation of magnetic moments at low temperatures. The photoemission spectra obtained at different photon energies suggest termination of the cleaved surface at cis-trans-As layers. The depth-resolved data show significant surface-bulk differences in the As and Ce core level spectra. The As 2 p bulk spectrum shows distinct two peaks corresponding to two different As layers. The peak at higher binding energy correspond to cis-trans-As layers and is weakly hybridized with the adjacent Ce layers. The As layers between Ce and Ag-layers possess close to trivalent configuration due to strong hybridization with the neighboring atoms and the corresponding feature appear at lower binding energy. Ce 3 d core level spectra show multiple features reflecting strong Ce-As hybridization and strong correlation. Intense f 0 peak is observed in the surface spectrum while it is insignificant in the bulk. In addition, we observe a features at binding energy lower than the well-screened feature indicating the presence of additional interactions. This feature becomes more intense in the bulk spectra suggesting it to be a bulk property. Increase in temperature leads to a spectral weight transfer to higher binding energies in the core level spectra and a depletion of spectral intensity at the Fermi level as expected in a Kondo material. These results reveal interesting surface-bulk differences, complex interplay of intra- and inter-layer covalency, and electron correlation in the electronic structure of this novel Kondo lattice system.